Skeletal muscle alterations in Marfan syndrome: a systematic review - Audrei R. Santos; Rita M. S. Gutierrez; Tatiana E. Koike; Talita C. Conte; Caroline C. Real; Nicolas A. Dumont; Elen H. Miyabara (Journal of Muscle Research and Cell Motility, 2025)

West Nile virus in Culex mosquitoes and dead birds from the San Gabriel Valley, California, 2021–2022 - Christine A. Mariskanish; Tristan Hallum; Sam S. Lee; Christian K. Fung; Thomas R. Tchingambu; Matthew A. Conte; Jun Hang (Archives of Virology, 2025)

The climatology of the deep particle flux in the oligotrophic western North Atlantic gyre, 1978–2022 - M.H. Conte; R. Pedrosa-Pàmies; J.C. Weber; R.J. Johnson (Progress in Oceanography, 2025)

Avenues towards reconciling wild and managed bee proponents - Alexis L. Beaurepaire; Katja Hogendoorn; David Kleijn; Gard W. Otis; Simon G. Potts; Theresa L. Singer; Samuel Boff; Christian Pirk; Josef Settele; Robert J. Paxton; Nigel E. Raine; Simone Tosi; et al. (Trends in Ecology & Evolution, 2025)

Correction to: Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)

A second locus contributing to the differential expression of the blue sensitive opsin SWS2A in Lake Malawi cichlids - Sri Pratima Nandamuri; Jane E. Schulte; Miranda R. Yourick; Benjamin A. Sandkam; Kristen A. Behrens; Melissa M. Schreiner; Maya Dayanim; Garrett Sweatt; Matthew A. Conte; Scott A. Juntti; Karen L. Carleton (Hydrobiologia, 2023)

Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)
Global pollinator declines threaten food production and natural ecosystems. The drivers of declines are complicated and driven by numerous factors such as pesticide use, loss of habitat, rising pathogens due to commercial bee keeping and climate change. Halting and reversing pollinator declines will require a multidisciplinary approach and international cooperation. Here, we summarize 20 presentations given in the symposium ‘Protecting pollinators and our food supply: Understanding and managing threats to pollinator health’ at the 19th Congress of the International Union for the Study of Social Insects in San Diego, 2022. We then synthesize the key findings and discuss future research areas such as better understanding the impact of anthropogenic stressors on wild bees.

Heavy metal background levels and pollution temporal trend assessment within the marine sediments facing a brownfield area (Gulf of Pozzuoli, Southern Italy) - Giovanna Armiento; Mattia Barsanti; Raffaela Caprioli; Salvatore Chiavarini; Fabio Conte; Cinzia Crovato; Maurizio De Cassan; Ivana Delbono; Maria R. Montereali; Elisa Nardi; Luisa Parrella; Massimo Pezza; et al. (Environmental Monitoring and Assessment, 2022)
In this study, site-specific natural background levels (NBLs) were determined for 18 elements (Al, As, Be, Cd, Co, Cu, Cr, Fe, Hg, K, Mn, Mo, Ni, Pb, Tl, U, V, and Zn) in two sediment cores collected offshore the Bagnoli-Coroglio brownfield site (Gulf of Pozzuoli, southern Italy) to accurately assess the degree of contamination and the historical trends in Heavy Metals (HMs) enrichment. This objective was pursued taking in account the high temporal and spatial variability of the geochemical properties of the area due to the local geothermal activity. Moreover, the temporal variation of Polycyclic Aromatic Hydrocarbons (PAHs) was investigated. 226 Ra was used as an extraordinary marker to confirm 210 Pb dating. It especially allowed defining the geochronological framework of the sediment core closer the brownfield up to around 1500, providing compelling support to correlate the investigated elements’ occurrences with natural geogenic dynamic. Sediment samples were accurately dated and analyzed for chemical and particle size composition. The contamination factor (Cf) and the pollution load index (PLI) showed very high enrichment of Cd, Cu, Hg, Pb, and Zn. The contamination profiles of HMs and PAHs follow the same pattern in both sediment cores, increasing from deep to upper layers. The highest contamination levels for HMs and PAHs were observed between 10 and 30 cm, corresponding to the periods of most intense industrial activity. Decreasing trends of pollutants were observed in the surface layers (0–10 cm), probably affected by a natural attenuation process due to the cessation of industrial activities.

Microencapsulated Lemongrass ( Cymbopogon flexuosus ) Essential Oil Supplementation on Quality and Stability of Silver Catfish Fillets during Frozen Storage - Cristine Rampelotto; Caroline S. Speroni; Lisiane Conte; Dirleise Pianesso; Isadora S. Machado; Renata F. Rodrigues; Natália M. Minuzzi; Taida J. Adorian; Bruna Klein; Roger Wagner; Bernardo Baldisserotto; Leila P. da Silva; et al. (Journal of Aquatic Food Product Technology, 2021)

Correction to: Inert gas narcosis in scuba diving, different gases different reactions - Monica Rocco; P. Pelaia; P. Di Benedetto; G. Conte; L. Maggi; S. Fiorelli; M. Mercieri; C. Balestra; R. A. De Blasi (European Journal of Applied Physiology, 2019)

Inert gas narcosis in scuba diving, different gases different reactions - Monica Rocco; P. Pelaia; P. Di Benedetto; G. Conte; L. Maggi; S. Fiorelli; M. Mercieri; C. Balestra; R. A. De Blasi (European Journal of Applied Physiology, 2019)

Preslaughter Anesthesia with Lippia alba Essential Oil Delays the Spoilage of Chilled Rhamdia quelen - Juliana C. Veit; Jaqueline Piccolo; Aline F. Scherer; Isadora S. Machado; Luana H. Maurer; Lisiane Conte; Bernardo Baldisserotto; Gessi Koakoski; Charlene C. Menezes; Vania L. Loro; Leonardo J. G. Barcellos; Berta M. Heinzmann; et al. (Journal of Aquatic Food Product Technology, 2018)

Improvement in carbohydrate and phlorotannin extraction from Macrocystis pyrifera using carbohydrate active enzyme from marine Alternaria sp. as pretreatment - A. Leyton; R. Pezoa-Conte; P. Mäki-Arvela; J-P Mikkola; M. E Lienqueo (Journal of Applied Phycology, 2017)

Total Mercury in Carnivorous Fish from Brazilian Southeast - M. S. Ferreira; A. N. Marques; R. O. R. Ribeiro; C. A. Conte; C. S. Carneiro; R. E. Santelli; A. S. Freire; S. C. São Clemente; E. T. Mársico (Bulletin of Environmental Contamination and Toxicology, 2015)

The antiatherogenic effect of bixin in hypercholesterolemic rabbits is associated to the improvement of lipid profile and to its antioxidant and anti-inflammatory effects - Sabrina Somacal; Cassieli G. Figueiredo; Andréia Quatrin; Amanda R. Ruviaro; Lisiane Conte; Paula R. Augusti; Miguel Roehrs; Ione T. Denardin; Jocieli Kasten; Marcelo L. da Veiga; Marta M. F. Duarte; Tatiana Emanuelli (Molecular and Cellular Biochemistry, 2015)

Potential allelopathic activity of Sideritis italica (Miller) Greuter et Burdet essential oil - A. Basile; R. C. Cobianchi; D. Rigano; F. Senatore; M. Bruno; S. Rosselli; B. Conte; S. Sorbo (Plant Biosystems, 2011)

Antioxidant activity in extracts from Leptodictyum riparium (Bryophyta), stressed by heavy metals, heat shock, and salinity - A. Basile; S. Sorbo; B. Conte; B. Golia; S. Montanari; R. Castaldo Cobianchi; S. Esposito (Plant Biosystems, 2011)

Survey of the presence of patulin in fruit juices - E. Bonerba; E. Ceci; R. Conte; G. Tantillo (Food Additives & Contaminants Part B-Surveillance, 2010)

Isolation and characterization of polymorphic microsatellites for the natural populations of barker frog Physalaemus cuvieri - M. Conte; L. J. Cançado; P. R. Laborda; M. I. Zucchi; G. V. Andrade; D. C. Rossa-Feres; S. Siqueira; A. P. Souza; S. M. Recco-Pimentel (Conservation Genetics, 2009)

Expression Profile and Distribution of Efhc1 Gene Transcript During Rodent Brain Development - Fábio F. Conte; Patrícia A. O. Ribeiro; Rafael B. Marchesini; Vinícius D. B. Pascoal; Joelcimar M. Silva; Amanda R. Oliveira; Rovílson Gilioli; Lourenço Sbragia; Jackson C. Bittencourt; Iscia Lopes-Cendes (Journal of Molecular Neuroscience, 2009)

The “in situ” expression of Human Leukocyte Antigen Class I antigens is not altered by cryopreservation in human arterial allografts - G. Pasquinelli; M. P. Pistillo; F. Ricci; M. Buzzi; P. L. Tazzari; L. Foroni; C. Manferdini; C. Ceccarelli; A. Stella; R. Conte (Cell and Tissue Banking, 2007)

Effects of 5 Hz subthreshold magnetic stimulation of primary motor cortex on fast finger movements in normal subjects - R. Agostino; E. Iezzi; L. Dinapoli; F. Gilio; A. Conte; F. Mari; A. Berardelli (Experimental Brain Research, 2007)

1,25-dihydroxyvitamin D3 protects human pancreatic islets against cytokine-induced apoptosis via down-regulation of the fas receptor - R. Riachy; B. Vandewalle; E. Moerman; S. Belaich; B. Lukowiak; V. Gmyr; G. Muharram; J. Kerr Conte; F. Pattou (Apoptosis, 2006)

Antiapoptotic role of p38 mitogen activated protein kinase in Jurkat T cells and normal human T lymphocytes treated with 8-methoxypsoralen and ultraviolet-A radiation - A. Cappellini; P. L. Tazzari; I. Mantovani; A. M. Billi; C. Tassi; F. Ricci; R. Conte; A. M. Martelli (Apoptosis, 2005)

Detection of ephemeral genetic sub-structure in the narrow endemic Abies nebrodensis (Lojac.) Mattei (Pinaceae) using RAPD markers - L Conte; C Cotti; R Schicchi; FM Raimondo; G Cristofolini (Plant Biosystems, 2004)

Effects of some dicarboxylic acids on the association of dissolved humic substances - A. Piccolo; P. Conte; R. Spaccini; M. Chiarella (Biology and Fertility of Soils, 2003)

Animal Transmissible Spongiform Encephalopathies and Genetics - U. Agrimi; M. Conte; L. Morelli; M.A. Di Bari; G. Di Guardo; C. Ligios; G. Antonucci; G.M. Aufiero; N. Pozzato; F. Mutinelli; R. Nonno; G. Vaccari (Veterinary Research Communications, 2003)

Severe 5-fluorouracil toxicity associated with a marked alteration of pharmacokinetics of 5-fluorouracil and its catabolite 5-fluoro-5,6-dihydrouracil: a case report - Bocci G.; Danesi R.; Allegrini G.; Innocenti F.; A. Di Paolo; Falcone A.; Conte P.; M. Del Tacca (European Journal of Clinical Pharmacology, 2002)

The effect of halogens on Zr diffusion and zircon dissolution in hydrous metaluminous granitic melts - Don R. Baker; Aida Conte; Carmela Freda; Luisa Ottolini (Contributions to Mineralogy and Petrology, 2002)

Polymerization of humic substances by an enzyme-catalyzed oxidative coupling - A. Piccolo; A. Cozzolino; P. Conte; R. Spaccini (The Science of Nature, 2000)

The solution structure of a monomeric, reduced form of human copper,zinc superoxide dismutase bearing the same charge as the native protein - Lucia Banci; I. Bertini; R. Del Conte; Roberto Fadin; Stefano Mangani; Maria Silvia Viezzoli (JBIC Journal of Biological Inorganic Chemistry, 1999)

Chronic Pulmonary Histoplasmosis in a Patient with a Recent History of Tuberculosis and Persistent Round Lung Lesions - M. A. Viviani; T. Masini; D. Conte; C. Trovato; R. Pometta (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Changes of the biophysical properties of calcium-activated potassium channels of rat skeletal muscle fibres during aging - D. Tricarico; R. Petruzzi; D. Conte Camerino (Pflügers Archiv - European Journal of Physiology, 1997)

Taxonomic implications of Prototheca and Chlorella cell wall polysaccharide characterization - Mario V. Conte; R. Scott Pore (Archives of Microbiology, 1973)